2022
DOI: 10.3390/antibiotics11030350
|View full text |Cite
|
Sign up to set email alerts
|

Antiseptic Agents for Chronic Wounds: A Systematic Review

Abstract: In many parts of the world, antiseptic agents remain non-indicated in chronic wound care. In the current context of bacterial resistance to antibiotics and the development of new-generation antiseptic agents, wound antisepsis represents an asset for the prevention of wound infection. We aimed to evaluate four common antiseptic agents in chronic wound care complete healing. The review protocol was based on the Cochrane Handbook for Systematic Reviews of Intervention and devised in accordance with the Preferred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 42 publications
0
10
0
1
Order By: Relevance
“…It was also shown that the injection of cold and acidic solutions of known antiseptics into the area of purulent wounds provides disinfection of the treated surface, but does not dissolve and remove thick and viscous pus [20,43]. It has been reported that the use of known antiseptic solutions according to current medical standards does not provide effective and rapid dissolution and removal of thick and sticky pus in the treatment of long-term non-healing purulent wounds, bedsores and trophic ulcers [44]. It has been established that the reason for the low effectiveness of traditional treatment of bedsores, trophic ulcers and many other purulent diseases, including COVID-19, is the absence of pyolytics in the medical standards of treatment of these diseases [7,20,41].…”
Section: Discussionmentioning
confidence: 99%
“…It was also shown that the injection of cold and acidic solutions of known antiseptics into the area of purulent wounds provides disinfection of the treated surface, but does not dissolve and remove thick and viscous pus [20,43]. It has been reported that the use of known antiseptic solutions according to current medical standards does not provide effective and rapid dissolution and removal of thick and sticky pus in the treatment of long-term non-healing purulent wounds, bedsores and trophic ulcers [44]. It has been established that the reason for the low effectiveness of traditional treatment of bedsores, trophic ulcers and many other purulent diseases, including COVID-19, is the absence of pyolytics in the medical standards of treatment of these diseases [7,20,41].…”
Section: Discussionmentioning
confidence: 99%
“…Antiseptics are a class of drugs that can prevent the growth or damage of microorganisms in living tissues or on the surface of living tissues. Halogenated compounds, alcohol-based agents, and biguanides are often used as antiseptics primarily for chronic wound care because they effectively inhibit bacterial reproduction and promote resistance to the external environment [ 51 , 52 ]. (4) Alginate dressing: Alginate dressing consists of alginate salts, which are highly absorbent and hemostatic and suitable for highly exuding wounds.…”
Section: Diabetic Wounds and Diabetic Dressingsmentioning
confidence: 99%
“…Хирургическая инфекция в стационарах проявляется тяжелым течением и часто не поддается стандартным методам лечения. Все это приводит к постоянному росту осложнений гнойнонекротических заболеваний и неблагоприятным исходам [1][2][3][4]. После радикальных хирургических вмешательств по поводу флегмон, абсцессов, некротизирующей инфекции часто образуются обширные раневые дефекты, требующие индивидуального подхода в скорейшем их закрытии методами пластической хирургии.…”
Section: Introductionunclassified